Сlinical case: social load is the predictor and preventer of somatization - Romaniv, Olexandr; Pohoriliak, Katherine (Psychosomatic Medicine and General Practice, 2017)
Somatization can lead to social dysfunction, problems at a workplace and increase the health care use. Thus, it is both clinical and public health problem. It is incredibly problem understand the psychosomatic disorders, especially in Ukraine. This article discusses the clinical care of a person who has sufficient level of social status and professional development, long suffering from anxiety-depressive disorders with somatic symptoms. The level of social load greatly influences to disorder severity, alternatively as the predictor and preventer of clinical features.